Tourist tax-fee as a mechanism of urban renovation and upgrade of tourist product: Implementation on the municipality of Athens - Vasiliki Delitheou; Georgios Papastamatiou (European Regional Science Association (ERSA), 2016)
Tourism has been an important factor for national and local development. Local taxes on tourism could increase local revenues which in turn could upgrade local environment. This paper proposes a model of urban renaissance and redevelopment of the local tourist industry, based on the levying of a tourist charge fee that will replenish a contributory mechanism which will provide a guarantee capacity to the hotel establishments, who will be able to create large investment projects in upgrading and modernising their existed infrastructure facilities, while at the same time this mechanism will also combine the contribution of funds coming from the E.U. funds, which will be used for the implementation of aesthetics interventions over the façade of the old and abandoned buildings. The imposition of a small tax- fee which will be provided to a significant number of tourist who will be offered overnight lodgings in a city, will have a much less pronounced impact on the tourist trade but a significant one on the busyness of this section, because through the re-circulated use of the funds, due to this wide guaranteed funding mechanism, the redevelopment of the already existed hotel establishments will be strengthened, while, through the benefits of this mechanism, new investments in hotel establishments will be held in less-favored regions of a city.
Keywords: L83; O18; 330; Tourism; taxes; local government revenues